The Origins of Federal Industrial Relations Systems: Australia, Canada and the USA - Patmore, Greg (Journal of Industrial Relations, 2009)
There are tensions in federal political systems over whether the central government or the states/provinces are the most suitable jurisdictions for dealing with the relationship between employers and unions. As integrated national economies developed, there are growing pressures on federal governments to intervene in industrial relations. States/provinces, however, might still maintain unique economic and social conditions that render federal legislation inappropriate. This article examines the development of federal jurisdictions in Australia, Canada and the USA up until the late 1940s. While Australia, unlike the other the two countries, had a constitution that provided for federal coverage of industrial relations, it was a limited power. Despite this, there was a gradual spread of federal coverage beyond that originally intended by the original framers of the Australian Constitution. The Canadian and US constitutions predate the rise of organized industrial relations. However, federal governments in these countries also increased their involvement in industrial relations to resolve disputes in key national industries such as railways and in response to critical events such as the Great Depression and World Wars, which challenged existing assumptions about industrial relations. While there was a trend towards the federal regulation of industrial relations, states and provinces still played a key role as innovators in both experimenting with new ways of regulating relations between employers and unions and imposing restrictions on the power of organized labour.
Keywords: Industrial relations; constitution; federalism; provinces; states